Effect of abnormal yolk sac, gestational sac and embryonic heart rate in pregnancy outcome - Jaiswal, Jyoti; Jaiswal, Anand Kumar; Patel, Geetanjali; Daharwal, Abha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The purpose of the study is to know the effect of abnormal yolk sac, abnormal gestational sac and abnormal embryonic heart rate on outcome of pregnancy in the tertiary care centre of Chhattisgarh. Methods: This prospective observational study included 50 pregnant females between 6-9 weeks gestation with singleton pregnancy attending antenatal clinic in a tertiary medical institution. Transvaginal sonography was carried out to quantify yolk sac characteristics. Abnormal yolk sac was defined according to Nyberg criteria. Results: Out of 50 cases, 25 cases had abnormal yolk sac, 23 cases had abnormal gestational sac and 22 cases had abnormal embryonic heart rate and heart rate was absent in 23 cases. Out of 50 cases, 32 got aborted and rest 18 cases had ongoing pregnancy beyond 20 weeks. Normal yolk sac diameter (YSD) (2-5 mm) showed 72.2% sensitivity, 62.5% specificity, 52% positive predictive value and 80% negative predictive value in predicting pregnancy outcome. Gestational sac diameter had 66.66% sensitivity, 53.12% specificity, 44.44% PPV and 73.91% NPV and for EHR had 22.22% sensitivity, 96.87% specificity, 80% PPV and 68.88% NPV. Conclusions: The embryos with abnormal YSD are highly associated with poor pregnancy outcome with good sensitivity and NPV. Present study indicates that the yolk sac measurement is reliable prognostic factor in predicting 1st trimester pregnancy outcome.